Remediação bio-eletroquímica do hormônio sexual sintético 17-α-etinilestradiol - Garcia, Luane Ferreira (2016)
Hormones are released constantly in sewage, originated by of human/animal excreta, or waste of pharmaceutical industries, not treated satisfactorily. The eviction of these pollutants in water resources produces great environmental impact, as disruption in animals’ endocrine system. The 17α-ethinylestradiol (EE2) is the most popular synthetic estrogen, which is found in water and in considerable concentrations. Several strategies are being studied to remedy this pollutant. Enzymes as laccases, which have low specificity, are able to oxidize various pollutants, thus suggesting their potential in the treatment of effluents. Another alternative are the electrochemical processes as electro-oxidation and electrocoagulation. The aim of this study was to evaluate the removal efficiency of the EE2 for biological or/and electrochemical process. The crude extract containing the laccase from Pycnoporus sanguineus was immobilized in Ca/Cu-alginate-chitosan beads. For partial characterization were determined optimum pH and optimum temperature of enzyme activity, for free and immobilized enzyme. Biological remediation was performed in these conditions: shaking (100 rpm); temperature at 28°C (± 2); times of 4, 8 and 24 hours; EE2 solution buffered at pH 4 and 5, and EE2 solution without addition of buffer. For the electrochemical remediation: magnetic stirring; voltage of 2.5, 5 and 7.5 V; times of 10, 20 and 40 minutes; pHs 5 and 7. For bio-electrochemical remediation the best conditions were used. In the remediation assays of the EE2 with immobilized enzyme, the best result was obtained for the support Ca-alginate-chitosan with 89.81% (± 2.71) removal, in sodium acetate buffer pH 5.0 and 24 hours of treatment. Under the same conditions to the free enzyme, 91.81% (± 0.86) of removal was obtained. For electrochemical remediation with titanium electrode, 86.21% (± 9.30) was removed in pH 7 phosphate buffer and 40 minutes. For sequential bio-electrochemical remediation, EE2 concentrations were below the limit of detection of the chromatograph, with the removal by immobilized enzyme acting in unbuffered solution. It can be concluded that the two technologies are very effective for the removal of the EE2.